VISUALISASI DAN MAKNA ANALISIS GEOSEMOTIK PAPAN NAMA DI PUSAT KOMERSIAL - Murti, Dhea Pratiwi Dhea; Syahrani, Agus; Asfar, Dedy Ari (Universitas Tanjungpura, 2025)
Signboards are a type of visual communication that we use on a daily basis as general markers to transmit information for specialized reasons. The geosemiotic theory technique is used in this study. The goal of the study is to thoroughly examine how signboards and the physical world interact. The Gaia Bumi Raya Shopping Center in Kubu Raya is the site of the study. The research design is qualitative and employs a descriptive method. Techniques for gathering data include interviews and documentation. The field's findings show 21 directional signboards with a white background and monolingual English, together with font selections and sign placement that are strongly tied to the physical environment. In this study, the method used is the descriptive method. The descriptive method is used by researchers to represent field data in the form of nameplates, reflecting the identity of Gaia Bumi Raya. This method is also very flexible and easy to use in field research, especially in recording observation results directly without data manipulation. The form of research used in this study is qualitative.